Traditional crafts: disappearing knowledge in the Greater Metropolitan Area of Costa Rica - Barrantes Jiménez, Celia (2024)
The paper presents a brief conceptual discussion around the conception of traditional crafts developed within the framework of a research activity through a reflective search toward their understanding. As a network of knowledge, beyond the end product, and with this element as the basis, the study checks the transition of craftsmanship development in the consolidation within the urban centers of Cartago (colonial time) and San José in the 19th century through the review of secondary sources. This reflection will show that traditional crafts are a diverse form of social organization interacting differently according to the ecosystemic, social, cultural, political, and economic conditions which will allow the validity or disappearance of the practice.